PENGEMBANGAN LKPD BERBASIS NATURE OF SCIENCE UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS - Pipit Wulandari; Yeni Widiyawati; Dwi Septiana Sari (Saintifika, 2019)
Abstract: The science process skill is one of the science learning goals. The aims of this study were to develop NOS based worksheet in environmental pollution to enhance students’ science process skills. This study was research and development which adapted the 4D model (Define, Design, Develop, Disseminate). This research was conducted at Multazam Junior High School. 20 students of VII grade was used as a subject in this research. The data collecting by an expert appraisal, teacher and student response towards worksheet questionnaire. The quantitative-descriptive technique was used in this research. The analysis data results showed that developed worksheet very good in the category. Therefore, it can be concluded that this develop worksheet is feasible to use science learning. Kata Kunci: nature of science, science process skills, worksheet